2015
DOI: 10.11607/jomi.3526
|View full text |Cite
|
Sign up to set email alerts
|

Crestal Bone Remodeling Around Implants Placed Using a Short Drilling Protocol

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Bratu et al and Mihali et al suggested the use of a short drilling implant protocol (sdip) during implant osteotomy preparations, supporting the significantly reduced duration [ 56 , 57 ]. The sdip consisted only of the use of the pilot drill and the final drill.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bratu et al and Mihali et al suggested the use of a short drilling implant protocol (sdip) during implant osteotomy preparations, supporting the significantly reduced duration [ 56 , 57 ]. The sdip consisted only of the use of the pilot drill and the final drill.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the conventional protocol, the sdip did not show any statistically significant difference in temperature increase and drilling torque [ 56 ]. In addition, there was no statistically significant difference on bone remodeling between the conventional and sdip 12 months after epicrestal implant placement, both showing around 1 mm of crestal bone loss [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several publications suggested that, reducing the number of drill steps is not compromising clinical results (22)(23)(24). Limiting the duration of surgical intervention to better healing and more patient satisfaction (25). According to Nadine Marheineke et al in 2018 (26), higher accuracy of implant preparations were generated by single step drill protocols, which might result in an increased primary stability.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were sent for Cone Beam Computed Tomography (CBCT) scans to evaluate bone dimension and implant positioning. A short drilling protocol was used and four to ten dental implants were placed in the edentulous arches followed by a 3-month period of osseointegration [10]. All the restoration bring multi-unit abutment at the day of insertion and a temporary full-arch restoration was made not more than 48 hours ( fig.…”
Section: Clinical and Laboratory Protocolmentioning
confidence: 99%